Towards a holistic and integrated Life Cycle Sustainability Assessment of the bioeconomy: Background on concepts, visions and measurements - Walther Zeug; Alberto Bezama; Daniela Thrän (Helmholtz-Zentrum für Umweltforschung (UFZ), 2020)
Current economic and social systems transgress several ecological planetary boundaries by far but without sufficiently fulfilling human needs and this in a globally unequal way, posing enormous challenges to political strategies and economic structures. To tackle these challenges, under a bioeconomy, a variety of industrial metabolisms, strategies and visions on substituting fossil resources by renewables and hereto associated societal transformations is formulated. Social, ecological and economic (holistic) sustainability, however, is not an intrinsic character of bioeconomy but rather a possible potential which has to be assessed. Life Cycle Assessments and Life Cycle Sustainability Assessments provide promising frameworks and methods for such holistic sustainability assessments, but face major challenges in regard to underlying sustainability concepts and implementation. First, we discuss and analyze the status quo of Life Cycle Sustainability Assessment especially in regard to underlying sustainability and economic concept and identify their strengths, weaknesses and research gaps. Secondly, we characterize the current bioeconomy discourse and propose a transdisciplinary, holistic and integrated framework for Life Cycle Sustainability Assessment. Based on this discussion and the proposed framework, holistic and integrated Life Cycle Sustainability Assessment can provide a transdisciplinary understanding and specific information on the absolute and relative holistic sustainability of provisioning systems to allow efficient and effective governance.
Keywords: 330; bioeconomy; holistic sustainability; sustainability assessment; SDGs; transdisciplinarity; LCA; LCSA; ILCSA; HILCSA